PERAN ORANG TUA TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS VIII-1 SMP NEGERI COKROAMINOTO KALABAHI TAHUN PELAJARAN 2024/2025 - Sibala, Ismawat; Amsidi, Mukmin (STKIP Muhammadiyah Kalabahi, 2025)
This study aims to analyze the role of parents in the motivation to learn mathematics of eighth-grade students in class VIII-1 at SMP Negeri Cokroaminoto Kalabahi for the 2023/2024 academic year. The research method used is a qualitative descriptive method. Data were collected through questionnaires, interviews, and observations of students, parents, and math teachers. The research results show that the role of parents has a significant impact on students' motivation to learn mathematics. Parents who are actively involved in supporting their child's learning activities, providing encouragement, and showing interest in their child's math achievements can enhance the student's motivation. Conversely, the lack of parental involvement in supporting mathematics learning can negatively impact students' motivation to learn. It was found that open communication between parents, students, and math teachers plays an important role in increasing learning motivation. Parents who allocate time to discuss their child's academic progress, help with assignments, and provide positive reinforcement can create a positive learning environment at home. Additionally, it was found that parents' positive attitudes towards mathematics and their involvement in mathematical activities outside of school, such as visits to mathematics museums or math discussions at home, can stimulate students' interest and motivation in the subject. Based on the results of this study, it is recommended that schools and parents collaborate to create more effective strategies to enhance the role of parents in supporting students' motivation to learn mathematics at the secondary school level.